Pairing transcutaneous vagus nerve stimulation with an intensive bimanual training in children and adolescents with cerebral palsy: study protocol of a randomized sham-controlled trial - Oldrati, Viola; Gasparroni, Verusca; Michelutti, Arianna; Ciricugno, Andrea; Borgatti, Renato; Orcesi, Simona; Fazzi, Elisa; Morandi, Alessandra; Galli, Jessica; Piccinini, Luigi; Maghini, Cristina; Arioli, Maria; et al. (Frontiers in Neurology, 2024)
Background: Gross motor function impairments and manual dexterity deficits are frequently observed in children and adolescents with Cerebral Palsy (CP), having a major impact on their activity level and autonomy. Improving manual dexterity and activity level of patients with CP is often the focus of rehabilitation. Novel and adjuvant treatment methods that could support the standard training also in chronic conditions are a research priority. The transcutaneous Vagus Nerve Stimulation (tVNS) is a non-invasive brain stimulation technique which provides a bottom-up stimulation of subcortical and cortical brain structures, enhancing brain GABA and Noradrenaline levels. This technique may play a pivotal role in brain plasticity, which has not been tested in CP patients before.Method: 44 children and adolescents with CP will be involved, treated in pairs in a randomized, double-blind, pre-post test study. The two groups will undergo the Hand-Arm Bimanual Intensive Therapy Including Lower Extremities (HABIT-ILE) for two consecutive weeks, with 3h daily sessions for five days per week, for an overall time interval of 30 hours; the training will be combined with the application for 75 minutes/day of active or sham tVNS, in separate, randomly allocated groups. The primary outcome measure will include the scores at the Assisting Hand Assessment and Box and Block Test, and at an ad-hoc visuomotor task evaluating manual visuomotor control. Secondary outcomes will include the scores at the Children's Hand Experience Questionnaire, Canadian Occupational Performance Measure, Melbourne Assessment of Unilateral Upper Limb Function, Gross Motor Function Measure, Vineland, Pediatric quality of life inventory. The evaluation points will include pre (T0), post (T1) and 3-month follow up (T2) assessments. Safety and tolerability will also be assessed.The results of this trial will assess whether tVNS can effectively boost the effects of an intensive twoweek bimanual training, in improving manual dexterity in children and adolescents with cerebral palsy, ensuring safety and tolerability throughout the intervention period.Trial registry number: NCT06372028 (ClinicalTrials.gov Identifier)